Pengabdian Sosialisasi SADARI pada Remaja Putri Upaya Pencegahan Kanker Payudara - Liliek Pratiwi; Endah Dian Marlina; Nur Fitri Ayu Pertiwi; Mudy Oktiningrum4; Harnanik Nawangsari (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
One of the most commo types of cancer in Indonesia is breast cancer, which is the leading cause of death for women. The purpose of the SADARI socialization service is to increase the awareness of adolescent girls about the importance of early detection through the Self Breast Check method (SADARI), this SADARI socialization service also aims to increase the understanding of adolescent gilrs about the importance of maintaining breast health from an early age. The methode used to increase understanding, this activity uses lectures and interactive discussion as well as simulations using leaflets, which were attended by 50 young women participating in the event. The results of the activity showed a significant increase in participants’ knowledge and their ability to perform SADARI correctly. They also point out that the importance of early detection has increased. In conclusion, this socialization helps adolescent girls understand and realize SADARI to be more proactive in preventing breast cancer.